Volume 6A: Pipeline and Riser Technology 2014
DOI: 10.1115/omae2014-23507
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich Pipes With Strain Hardening Cementitious Composites (SHCC): Numerical Analyses

Abstract: Sandwich pipes (SP) combining high structural resistance with thermal insulation have been considered as an effective solution for using in ultra deepwater pipelines. Research has been conducted at COPPE/UFRJ with different core materials aiming to develop qualified pipes to transport deepwater oil and gas, especially for the pre-salt reservoirs in offshore Brazil. SPs using SHCC material are easy to manufacture and cost-effective. Moreover, the composition of the SHCC material can be controlled to achieve str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[9] and Fu et al. [10] have conducted experimental and numerical studying on the collapse pressure of SP-filled lightweight cement-based material. Three SP samples were tested experimentally and numerically analyzed.…”
Section: Finite Element Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] and Fu et al. [10] have conducted experimental and numerical studying on the collapse pressure of SP-filled lightweight cement-based material. Three SP samples were tested experimentally and numerically analyzed.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Fu et al. [10] performed the numerical analysis of collapse and collapse propagation of SPs with SHCC material core.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the studies of Sato and Patel (2007), Arjomandi and Taheri (2011), the present study accounts for shear deformation effects within the core, and for the presence of internal pressure. Fu et al (2014)…”
Section: Sandwich Pipes Under External Pressurementioning
confidence: 99%
“…Researchers have conducted a large number of experiments to study the buckling propagation behavior of the sandwich pipe under external pressure. Pasqualino et al [20], Lourenco et al [21], Fu et al [22], Gong et al [23], and Gong et al [24] studied the effect of interlayer bonding on the buckling propagation pressure of sandwich pipes through small-scale experiments and numerical simulations and established empirical expressions through numerical simulations. Gong et al [25] studied the buckling propagation of sandwich tubes with integral buck arrestors under external pressure under different interfacial bonding conditions through high-pressure tank tests and found that interlayer bonding not only affects the collapse pressure but also has a great influence on the buckling propagation.…”
Section: Introductionmentioning
confidence: 99%